ASIGNACIÓN DE FUNCIONES EN EL CENTRO DE SALUD PÚBLICA DEL CANTÓN ALFREDO BAQUERIZO MORENO, PROVINCIA DEL GUAYAS - Lascano Mora, Karen Tamara (2018)
he Public Health Center Alfredo Baquerizo Moreno was created in the year 2002 and then, over the years, modifications were made to its facilities in such a way that it was rebuilt and, with the mandate of the current Mayor Nicolás Ugalde Yánez, the inauguration of the new facilities, which are of great help when providing quality care to users of this sector and its surrounding areas.